Lateral-flow device for the diagnosis of invasive aspergillosis: a systematic review and diagnostic meta-analysis - Yuqing Fan; Xue Shang; Yan Wang; Yinghua zhang; Xiuxia Li; Kehu Yang; Haidi Lv; Kangle Guo (BMC Infectious Diseases)
Abstract Background Early diagnosis of invasive aspergillosis (IA) can significantly enhance patient survival rates; however, accurately diagnosing IA remains a formidable challenge. Lateral flow device (LFD), as a non-invasive detection method, have been extensively investigated in numerous clinical studies. The objective of this study was to elucidate the diagnostic accuracy of LFD in detecting IA through a meta-analysis. Methods The PubMed, Embase, and Web of Science database were searched to obtain clinical studies on the diagnosis of IA by LFD. A random-effects meta-analysis with a bivariate hierarchical model was used, the estimates and 95% confidence intervals (CI) were used to present pooled sensitivity, specificity, and summary receiver operating characteristic curves (SROC). Results Twenty-five cohort or case-control studies were included. The pooled sensitivity of LFD in the diagnosis of IA was 0.67 (95% CI: 0.57–0.75), specificity was 0.90 (95% CI: 0.85–0.93), diagnostic odds ratio was 15.70 (95% CI: 9.69–25.44), the area under the SROC curve (AUC) was 0.87 (95% CI: 0.82–0.93). Subgroup analysis showed that the sensitivity of bronchoalveolar lavage fluid specimen was higher than serum specimen (0.72, 95% CI: 0.67–0.78 vs. 0.49, 95% CI: 0.41–0.56), bronchoalveolar lavage fluid specimens also have higher diagnostic accuracy (AUC = 0.89). Conclusions LFD is an effective technique for the detection of IA infection, but attention should be paid to the influence of specimen source on the accuracy of this technique.